Physicochemical and Nutritional Properties of Different Non-Bovine Milk and Dairy Products: A Review - Siddiqui, Shahida Anusha; Salman, Sayed Hashim Mahmood; Redha, Ali Ali; Zannou, Oscar; Chabi, Ifagbemi B.; Oussou, Kouame F.; Maqsood, Sajid (Elsevier Sci Ltd, 2024)
Functional foods derived from milk are essential for human health, including fermented milk, dairy beverages, cheeses, and dairy sweets. The nutritional composition of different milk sources varies, impacting the qualities of resultant functional foods. Goat milk has health-promoting compounds, including calcium, medium-chain fatty acids, and a-casein. Sheep milk has significant amounts of vitamins A, C, thiamine, and folic acid. Buffalo milk is regarded as a nearly complete food item in the human diet and provides greater levels of a-and k-casein relative to bovine milk. Mare and donkey milk is rich in carbohydrates and proteins, with low-fat contents, making it a suitable dietary option. Camel milk is rich in calcium, potassium, vitamin A, and the absence of b-lactoglobulin, a major allergy compared with bovine milk. This review highlights the nutritional properties of non-bovine milk sources, which could be potentially used in the dairy industry similar to that of bovine milk. (c) 2023 Elsevier Ltd. All rights reserved.
Bhowmik, Shuva/0000-0002-3858-7359; Nirmal, Nilesh/0000-0003-2732-4534; Zannou, Oscar/0000-0003-1227-1265; Maqsood, Sajid/0000-0003-2099-8392; Chabi, Ifagbémi Bienvenue/0000-0002-9987-9080